Network Analysis of Power Transmission System Topology - Muhammad, jawad; Hushairi, Zen; Faisal, Rahman; Muhammad, Ali; Saqib, Salahuddin; Rahat, Nasim; Arshad, Mehmood (ENCON 2013, 2013)
Power system complex analysis has put researchers in demanding and challenging position to avoid unwanted events in interconnected network.Power system engineers have focused on power transmission and distribution issues in depth for stabilized operation of non autonomous network. Power system model dynamics vary at much faster rate so complex system may suffer from local and global blackouts. This paper highlights the properties of power grids infrastructure using techniques and methodologies of Complex Network Analysis (CNA). The discussion is conducted on different measures of network structure using IEEE 30 and IEEE 57 bus data. The computed results and structure of power network have important implication on reliability and security of the systems.